(untitled) (Research, Society and Development, 2020)
Objective: To compile information on the disease noma, in order to facilitate the clinical conduct of dental surgeons. Methods: It is an integrative review of the literature in which they were included articles published between 2015 and 2020, in portuguese or english, available for free and in full, and indexed in PubMed and SciELO. Results: After the synthesis of search, and application of filters and eligibility criteria, 18 articles were selected to be compatible with the theme addressed, performing a synthesis on this information in later stages corresponding to the importance and knowledge of dental surgeons and other health professionals about the noma disease. Conclusion: It becomes evident the need of knowledge by dental surgeons and other professionals in the health area on the particularities that involve the Noma disease. The authors reinforce the development of preventive actions through programs of health in primary care, aiming at the early diagnosis, lower mortality and effective treatment.